2007
DOI: 10.1016/j.cell.2007.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Prevents Bone Loss via Estrogen Receptor α and Induction of Fas Ligand in Osteoclasts

Abstract: Estrogen prevents osteoporotic bone loss by attenuating bone resorption; however, the molecular basis for this is unknown. Here, we report a critical role for the osteoclastic estrogen receptor alpha (ERalpha) in mediating estrogen-dependent bone maintenance in female mice. We selectively ablated ERalpha in differentiated osteoclasts (ERalpha(DeltaOc/DeltaOc)) and found that ERalpha(DeltaOc/DeltaOc) females, but not males, exhibited trabecular bone loss, similar to the osteoporotic bone phenotype in postmenopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
775
11
9

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 901 publications
(841 citation statements)
references
References 52 publications
26
775
11
9
Order By: Relevance
“…But, there still remains the possibility that signaling linked to ER would be altered even though the immunolocalization of ER was unchanged. Recently, the proapoptotic effect of estrogens on osteoclasts was reported to be mediated by an increase in Fas ligand production by osteoclasts [44], and in vitro studies showed that estrogens stimulate Fas ligand expression in osteoblastic cells which are precusors of osteocytes [43]. However, we showed no obvious difference in the number of TUNEL-positive osteoblasts and osteocytes even after the OVX.…”
Section: Immunolocalization Of Er and Tunel-positive Osteocytes In Tcontrasting
confidence: 51%
See 1 more Smart Citation
“…But, there still remains the possibility that signaling linked to ER would be altered even though the immunolocalization of ER was unchanged. Recently, the proapoptotic effect of estrogens on osteoclasts was reported to be mediated by an increase in Fas ligand production by osteoclasts [44], and in vitro studies showed that estrogens stimulate Fas ligand expression in osteoblastic cells which are precusors of osteocytes [43]. However, we showed no obvious difference in the number of TUNEL-positive osteoblasts and osteocytes even after the OVX.…”
Section: Immunolocalization Of Er and Tunel-positive Osteocytes In Tcontrasting
confidence: 51%
“…Thus, reduced-sclerostin did not appear to be associated with diminished ER in osteocytes in the mesial region. Other studies suggested a proapoptotic effect of estrogens on osteoclasts and osteoblasts [43,44], and therefore, it was necessary to confirm whether the reduced amount of sclerostin would be It is well known that OVX stimulates osteoclastic differentiation and subsequent bone resorption in long bones, and also shows the similar effects in alveolar bone [16][17][18][19][20][21][22].…”
Section: Immunolocalization Of Er and Tunel-positive Osteocytes In Tmentioning
confidence: 99%
“…We generated mice doubly deficient in p85a and p85b, which are dominantly expressed in the osteoclast lineage. Because homozygous deletion of Pik3r1, which encodes p85a, p55a, and p50a, results in perinatal lethality, (34) we crossed Pik3r1 F/À mice (25) with Ctsk Cre/þ mice (27) to obtain osteoclast-specific Pik3r1 knockout (Pik3r1 DOc/À ) mice. We mated Pik3r1 DOc/À mice with Pik3r2 À/À mice (26) to generate mice deficient in both p85a and b (Pik3r1 DOc/À Pik3r2 À/À mice).…”
Section: Resultsmentioning
confidence: 99%
“…Mice and the in vivo analysis of bone tissues Pik3r1 F/F , (25) Pik3r2 À/À , (26) CtsKCre transgenic, (27) and Akt pleckstrin homology domain-green fluorescent protein (AktPH-GFP) transgenic mice (28) were previously generated and are described elsewhere. Because a small population of osteoclasts from CtsKCrePik3r1 F/F mice still expressed p85a, CtsKCrePik3r1 F/F we mated mice to Pik3r1 þ/À mice to generate CtsKCrePik3r1 F/À (Pik3r1 Doc/À ) mice.…”
Section: Methodsmentioning
confidence: 99%
“…Estrogen has been shown to inhibit osteoclastogenesis via ER␣ (Nakamura et al, 2007), and kaempferol and quercetin also shows potent inhibitory effect on in vitro osteoclastic bone resorption (Wattel et al, 2003). Thus, kaempferol and quercetin in TSZ may also exert their antiosteoporotic effect not only by promoting osteoblastogenesis but also by inhibiting osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%